Emerging Antimicrobial Research against Superbugs: Perspectives from a Polymer Laboratory - Ganewatta, Mitra S. (J S C Acad Sci, 2017)
Infectious diseases caused by drug-resistant microorganisms have become a major contributor for human morbidity and mortality. To overcome such threats, we have developed various antimicrobial agents using natural product derivatives and metallopolymers. Abundant biomass such as resin acids can be utilized to prepare cationic polymers for inhibiting a variety of bacteria. These polymers have been used in solution as well as surfaces as antimicrobial materials with low cytotoxicity. In addition, a class of charged metallopolymers have been developed to kill superbugs such as MRSA.